Development of a Better Solid Waste Management Program for Sustainable Development in a Residential Subdivision - Almaden, Antoniette M. (Future Science / FSH-PH Publications, 2021)
Proper implementation of Solid Waste Management (SWM) is an essential part for the protection of the residents’ health, safety and environmental quality. SWM methods have been adapted by many residential subdivisions into a more practical and effective option to establish sustainability based on the reduce, reuse, and recycle principles. This study aims to contribute a solution to the challenging operation of solid waste management in Modena Mactan subdivision (1) to comprehensively describe the homeowner’s status classification and demographic characteristics, (2) to evaluate volume of waste produced and recycled waste revenue collected, (3) to recognize homeowner’s perception on the current waste management status, and (4) to showcase feasible approaches for sustainable waste management program. The study applied the descriptive research design and was carried out to 93 homeowners who went through the (house-to-house) paper-pencil-questionnaire survey. Results showed that the subdivision produced an average of 33 tons or 16.974 kilograms of solid waste per household per month, and generated an amount of 1,369 PHP or 27.41 USD revenue from the segregated recyclable waste collected from August 1-28, 2021. Moreover, about 87% of the respondents found convenient and sought to change in paperless system. Conclusively, it was revealed that 74% of the respondents found the recycling incentive scheme more inclusive as a feasible approach for waste management strategy to sustain the solid waste management program in Modena Mactan subdivision, Basak, Lapu-Lapu City, Cebu, Philippines.